A categoria sintática aposto sob a ótica da referenciação: um termo acessório ? - Masson, Solange Passos (2008)
In this study we will present a general description of the term apposition, based on its syntactic aspect, the occurrence of which will be seen from the point of view of referencing. Our aim is to demonstrate it in text, through the activity of construction and reconstruction of discourse objects. The analysis of the occurrences will be carried out in accordance with the classification of the types of apposition according to Azeredo (2002) and the classification of the semantic-discursive functions of Koch & Elias (2004). To use these categories, we will work with a simple noun syntagma, an apposition formed by a noun syntagma with only one nucleus (noun or pronoun), or by a nucleus and a determiner (numeral article or adjectival pronoun); and also with expressions starting with an adjective (or participle in the function of adjective), in cases which function as modifiers of an implicit central nucleus (complex noun syntagmas, to characterise the structure of apposition in its wide sense). We believe that to identify apposition as a mere accessory term is to annul an important discursive function: that of re-categorising a referent and contributing to the development of referents.